2019
DOI: 10.1042/bsr20190744
|View full text |Cite|
|
Sign up to set email alerts
|

A functional polymorphism rs10830963 in melatonin receptor 1B associated with the risk of gestational diabetes mellitus

Abstract: The melatonin receptor 1B (MTNR1B) polymorphism rs10830963 C>G has been reported to be associated with the risk of gestational diabetes mellitus (GDM) with inconsistent results. To clarify the effect of the polymorphism on the risk of GDM, a meta-analysis therefore was performed. Pooled OR with its corresponding 95%CI was used to estimate the strength of the association. Totally 14 eligible studies with a number of 5033 GDM patients and 5614 controls were included in this meta-analysis. Results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
0
16
1
2
Order By: Relevance
“…Conflictingly, the authors reported "0.99-0.99-0.99" as OR values [1] -of unknown origin -for our study (labelled as "Rosta et al" on Figures 2-3-4) in the forest plots on the risk of GDM associated with rs10830963 ("CG vs. CC" and "GG vs CC" and "C vs G", respectively). Despite that we did specifically report the minor (G) allele frequencies (MAF) in our study as 0.36 in the GDM group and 0.28 in the control group, these MAF data were apparently also wrongly indicated in the meta-analysis (MAF values of "0.33 and 0.30" in Table 1, respectively).…”
Section: Dear Editorcontrasting
confidence: 53%
“…Conflictingly, the authors reported "0.99-0.99-0.99" as OR values [1] -of unknown origin -for our study (labelled as "Rosta et al" on Figures 2-3-4) in the forest plots on the risk of GDM associated with rs10830963 ("CG vs. CC" and "GG vs CC" and "C vs G", respectively). Despite that we did specifically report the minor (G) allele frequencies (MAF) in our study as 0.36 in the GDM group and 0.28 in the control group, these MAF data were apparently also wrongly indicated in the meta-analysis (MAF values of "0.33 and 0.30" in Table 1, respectively).…”
Section: Dear Editorcontrasting
confidence: 53%
“…Conflict results were also observed with respect to studies on WBC [ 15 , 26 , 30 ]. On the other hand, there is an extensive body of literature identifying blood CRP and WBC as an independent and relatively strong predictive marker for outcomes after ischemic stroke [ 31 – 33 ], it is reasonable for expecting these associations in aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…That may be explained in part by considering that this polymorphism has been consistently associated with a higher risk of gestational diabetes in women [34][35][36]38,40]. In a recent meta-analysis carried out by Huang et al [72], including more than 5000 multi-ethnic gestational diabetes cases and 5000 controls, they confirmed the significant association between the MTNR1B-rs10830963 and gestational diabetes. The estimated OR is 1.47 (1.24-1.73) in Caucasians.…”
Section: Discussionmentioning
confidence: 88%